Phytochemical Analysis and Antioxidant Activity of Aqueous Extract of Ficus septica Leaves from Sabah, Malaysia - Senty Vun-Sang; Mohammad Iqbal (UNIMAS, 2023)
Medicinal plants have long been used as primary antidotes for a variety of ailments, including tuberculosis, heart diseases, cancer, wound healing, asthma, diabetes mellitus, hypertension, pharyngitis, etc. Medicinal plant of Ficus septica Burm. f. (Moraceae) is a subtropical tree commonly known as the ivory fig, septic fig or white-veined fig. The present work aims to investigate the antioxidant activity, phenolic and flavonoid content, and qualitative screening of various phytochemicals in aqueous extracts of F. septica leaves. Total phenol and flavonoid contents were calculated using Folin-Ciocalteau and aluminium chloride reagents. The antioxidative effect of F. septica was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. Ficus septica was found to contain 27.32 ± 0.03 mg/g total phenolics expressed as gallic acid equivalent and 12.65 ± 0.00 mg/g total flavonoid expressed as catechin equivalent. In addition, the leaf extracts were found to contain various secondary metabolites such as alkaloids, flavonoids, tannins, saponins, steroids and triterpenoids. The ability of F. septica to scavenge the DPPH radical was determined by its IC50 value. The IC50 value of F. septica was 4.45 µg/mL. Inferred from the presence of phytochemicals, total phenolic and flavonoid content, and antioxidant activity of the plant, F. septica could be a potential addition to pharmaceutical products to improve human health by participating in the antioxidant defence system against the production of free radicals.